Mental Resilience of High School Adolescents Victims of Bullying in Semarang - Suerni, Titik; Rochmawati, Dwi Heppy (Journal of Advanced Multidisciplinary Research, 2024)
The task of healthy mental development in adolescents is to search for self-identity. Adolescents spend more time and socialize with peers. Differences in values, physical appearance, perception, hopes and ideals are the background for the creation of several problems among adolescents. This causes adolescents to become victims of Bullying from other adolescents who feel superior. This study aims to describe the mental resilience of adolescents who are victims of Bullying. The study was conducted using a descriptive analytical method. The sampling technique in the study used total sampling with a sample size of 54 respondents. Most of the respondents were female, 34 people (62.96%); aged 16 years, 25 people (46.30%); and living with parents, 48 people (88.89%). Moderate bullying incidents were experienced by 27 respondents (50%) and adolescent victims of bullying had moderate mental resilience, namely 28 respondents (51.85%). Conclusion: Therapy is needed in subsequent studies to overcome the mental condition of adolescent victims of bullying.